Entrevista com Pauline Kaldas - Campello, Priscila Campolina de Sá (Scripta, 2017)
Entrevista com a escritora egípcio-estadunidense Pauline Kaldas. Pauline Kaldas is the author of Egyptian Compass, a collection of poetry, Letters from Cairo, a travel memoir, and The Time Between Places, a collection of short stories. Her most recent book is Looking Both Ways, a collection of essays. She also co-edited Dinarzad’s Children: An Anthology of Contemporary Arab American Fiction. Her work has appeared in a variety of anthologies, including Inclined to Speak, Others Will Enter the Gates, and Home: An Imagined Landscape. She was awarded a fellowship in fiction from the Virginia Commission for the Arts, the Silver Award for Dinarzad’s Children from ForeWord Magazine Book of the Year Awards, and the RAWI Creative Prose Award. Kaldas was born in Egypt and immigrated with her parents to the United States at the age of eight in 1969. She is Professor of English and Creative Writing at Hollins University in Roanoke, Virginia.